2023
DOI: 10.3390/su15010884
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Common Ground of Sustainability and Resilience in the Building Sector: A Systematic Literature Review and Analysis of Building Rating Systems

Abstract: Over the last ten years, due to the increase in frequency and severity of climate change effects, resilience in buildings has become a growing topic in the current global discussion on climate change adaptation. Designing both sustainable and resilient constructions would help to face such effects; however, sustainability and resilience in design have been mostly treated separately so far. Since sustainability has been considered more than resilience, paying deeper attention to the latter is indispensable to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The improvement of organizational resilience necessitates that sustainable innovation in a specific field have a collective meaning of how and why to innovate to attain a more strategic advantage (Linnenluecke, 2017). For Felicioni, Lupíšek, and Gaspari (2023) in their study of exploring the common ground of sustainability and resilience in Europe found out that institutions which are successful in achieving sustainability in the face of disruptions, intense competitive pressures, engage in detailed assessments of the marketplace and adopt specific and focused strategies to become resilient, adapting to marketplace and innovating.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The improvement of organizational resilience necessitates that sustainable innovation in a specific field have a collective meaning of how and why to innovate to attain a more strategic advantage (Linnenluecke, 2017). For Felicioni, Lupíšek, and Gaspari (2023) in their study of exploring the common ground of sustainability and resilience in Europe found out that institutions which are successful in achieving sustainability in the face of disruptions, intense competitive pressures, engage in detailed assessments of the marketplace and adopt specific and focused strategies to become resilient, adapting to marketplace and innovating.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Buildings and urban environments are expected to operate under new climate conditions they might not be well prepared against. This task has become even more pressing due to the limited availability of an operational climate resiliency rating system in the market (Felicioni et al, 2023). Against this backdrop and the clear shift in both policy and market domains towards incorporating smart building rating systems, this paper has undertaken the crucial task of examining the extent to which four prominent smart building rating systems-Smart Readiness An overview of the sectoral performance of each system.…”
Section: Conclusion and Closing Remarksmentioning
confidence: 99%
“…Moreover, overcoming these shortcomings can be achieved when sustainability rating systems are applied in conjunction with smart building rating systems. The findings of Felicioni et al (2023) has showed that sustainable rating systems explicitly address among other the water efficiency, site ecology as well as the transportation system. These are those sectors where the reviewed smart building rating systems failed.…”
Section: Conclusion and Closing Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting on recent developments, Felicioni et al argue that a focus on sustainability has meant that the concept of resilience has been overlooked [50]. The authors claim that 'synergies' between the concepts provide opportunities for integration in building design to mitigate the worst aspects of climate change.…”
Section: Current Researchmentioning
confidence: 99%